LISTA DE LAS ESPECIES CHILENAS DE LA FAMILIA VESPIDAE (HYMENOPTERA: VESPIDAE) - Willink, A.; Chiappa, E. (Acta Entomológica Chilena, 2022)
This paper presents a checklist of the currently recognized species of vespids in the chilean area.